OIDDE Learning Model through Integrated Field Studies Abroad to Develop Ethical Decision Skills of Candidate Biology Teachers: Indonesian Perspective - Husamah; Yuni Pantiwati; Atok Miftachul Hudha (ÜNİVERSİTEPARK Limited, 2017)
This study aimed to describe the ethical problems, valuable experience, and ethical decision-making abilities about the environment by students through the application of OIDDE models on integrated field studies abroad. Descriptive data analysis techniques were used on existing data. Environmental ethical problems that arose are the use and exploitation of natural resources, pollution, lack of public facilities' cleanliness, poaching, and environment arrangement problems. Valuable experiences gained by students were: 1) Malaysia Highway Rest Area: plants flourish and the birdlife is undisturbed; 2) Malacca River: transformed into a clean and beautiful area; 3) Putrajaya: concerns raised about environmental balance and sustainability; 4) Sentosa Island: various modern amusement rides prepared for enjoyment in line with environmental principles. Ethical decisions taken were: 1) environmental functions and sustainability should be referenced in development; 2) amusement rides developed in line with environmental consideration; 3) pattern of consumption and human activities to avoid resultant pollutants as much as possible; 4) use of environmentally friendly facilities should become a lifestyle choice; and 5) consistently implement environment regulations.